Robin Hood : the man behind the myth - Phillips, Graham, 19..-; Keatman, Martin, 19..- (Michael O'Mara books, 1995)
"Although searches have been made for an historical Robin Hood, little or no evidence has been found. Indeed if Robin was a Sherwood outlaw during the period in which the modern story is set - the 1190s, when Richard I was absent on the Third Crusade - the historical records in Nottingham reveal no such character." "However in the county records of Yorkshire and the ecclesiastical archives of York Minster, historical detectives Graham Phillips and Martin Keatman have discovered remarkable new evidence that Robin Hood did exist historically, but in a different place and at a different time. The true story of Robin Hood originated not in Nottinghamshire but in Yorkshire. Robin was not the disinherited Earl of Huntington but a peasant revolutionary from Wakefield. The original story was set not in the 1190s but in the 1320s." "This vital new evidence at last allows the authors to reveal the man behind the myth, Robin Hood's true identity and his role in British history. And in overgrown woodland beside the ruins of an ancient priory, the burial site of the world's most famous outlaw is revealed."